2022
DOI: 10.1002/mabi.202200092
|View full text |Cite
|
Sign up to set email alerts
|

PLGA Cage‐Like Structures Loaded with Sr/Mg‐Doped Hydroxyapatite for Repairing Osteoporotic Bone Defects

Abstract: Poly(lactic-co-glycolic acid) (PLGA)-based porous structures have a widespread application in bone defects. To solve its flaws in the bone application, hydroxyapatite (HA) is often introduced into PLGA-based systems, and ion doping endows HA with more biological activity. In osteoporotic bone defects, the decreased activity of osteoblasts and the hyperactive osteoclasts results in slow bone repair. Strontium (Sr) can promote bone regeneration and inhibit bone resorption and has been used in the treatment of os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Micro-CT angio-graphy analysis revealed that at 4 weeks post-operation, the defects implanted with the PTM scaffold exhibited a greater formation of new blood vessels compared with scaffolds without Mg 2+ . In another case, Yu et al 40 prepared a PLGA cage structure loaded with Sr 2+ -and Mg 2+ -doped HA (Sr/ Mg@HA/PLGA-CAS). Results from in vitro cell experiments showed that the expression levels of ALP, BMP2, CoL-I, and OCN in the Sr/Mg@HA/PLGA-CAS group were 1.96-fold, 2.33fold, 15.32-fold, and 1.99-fold higher, respectively, compared with the PLGA-CAS group, indicating that the Sr/Mg@HA/ PLGA-CAS exhibited a strong osteogenic differentiation capability.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
“…Micro-CT angio-graphy analysis revealed that at 4 weeks post-operation, the defects implanted with the PTM scaffold exhibited a greater formation of new blood vessels compared with scaffolds without Mg 2+ . In another case, Yu et al 40 prepared a PLGA cage structure loaded with Sr 2+ -and Mg 2+ -doped HA (Sr/ Mg@HA/PLGA-CAS). Results from in vitro cell experiments showed that the expression levels of ALP, BMP2, CoL-I, and OCN in the Sr/Mg@HA/PLGA-CAS group were 1.96-fold, 2.33fold, 15.32-fold, and 1.99-fold higher, respectively, compared with the PLGA-CAS group, indicating that the Sr/Mg@HA/ PLGA-CAS exhibited a strong osteogenic differentiation capability.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
“…Pham et al [84], Cao et al [85] and Zheng et al [86] prepared a hydroxyapatite coating with good osteogenic activity on the surface of the substrate material by plasma spraying. In our previous study Yu et al [87] prepared a porous PLGA cage microsphere loaded with strontium and magnesium-doped hydroxyapatite. This porous system improves cell adhesion, angiogenesis and osteogenic differentiation.…”
Section: Calcium Phosphate Coating Induces Osteogenesismentioning
confidence: 99%
“…Anti-tumour and osteogenesis [78] Gel (Fe3O4/GOx/MgCO3 @PLGA) [79] Chemical composition Calcium phosphate PLGA cage-like structures loaded with Sr/Mg-Doped hydroxyapatite Promote osteogenic differentiation, induce angiogenesis, inhibit osteoclast differentiation [87] HA was coated with aluminium/bioplastic scaffolds by hydrothermal method…”
Section: T a B L E 1 (Continued)mentioning
confidence: 99%
“…Previous studies have demonstrated that PLGA treated with HA can enhance hydrophilicity, neutralise the acidic microenvironment arising from PLGA degradation, and increase surface roughness, potentially enhancing cell adhesion [26,27]. Yu et al [28] incorporated strontium-doped HA (Sr@HA) and magnesium-doped HA (Mg@HA) onto alkali-treated PLGA cage-like structures (PLGA-CAS) to form multifunctional Sr/Mg@HA/PLGA-CAS microspheres. These microspheres demonstrated the ability to stimulate osteogenesis and angiogenesis while inhibiting osteoclastic differentiation.…”
Section: Introductionmentioning
confidence: 99%